FORMATION OF THE COMMUNICATIVE CULTURE OF THE CONDUCTOR OF THE ORCHESTRA IN THE PROCESS OF CREATIVE ACTIVITY - Pastushok, Taras (International Journal of Innovative Technologies in Social Science, 2021)
This article analyzes the role of communicative culture in fostering creative relationships between the conductor and members of the orchestra. Besides, the structural stages of mutual communicative communication were identified. In this research the author proclaimed that the communication and creative interaction between the conductor of the orchestra and its members takes place in the form of creative dialogue, because the conductor communicates with the orchestra through a conductor’s gesture and facial expressions. However, the previous interpretation of artistic material (comments, instructions, requests, explanations of technical material and means of expression (dynamics, strokes, accuracy of rhythmic elements of the work, etc.)) is due to the communicative interaction of speech communication. The main means of communication between the conductor and the orchestra is the creative process. In this regard, at the final stage of dialogue between the conductor and the members of the orchestra, the communicative abilities of the conductor play a special role in achieving the highest quality result of creative interaction and cooperation.